Microglial Self-Recognition STINGs in A-T Neurodegeneration. Issue 11 (November 2019) - Ferro, Austin; Sheeler, Carrie; Cvetanovic, Marija
Abstract : Microglial inflammation is often seen as a secondary event in neurodegeneration. A recent study by Song et al. demonstrates that loss of ataxia telangiectasia mutated (ATM) activates microglia through the cytosolic DNA sensor STING. This highlights the ability of microglia to recognize and respond to self-DNA, with potentially neurotoxic consequences.